Analyzing The Role of Fur-Friends in Mental Well-Being: Comparing Mental Well-Being of Pet Owners and Non-Owners - Jervin Dinglasan Quicho; Jesslaine Angela Sanchez; Alexandra Nicole P. Mendoza (International Journal of Multidisciplinary: Applied Business and Education Research, 2026)
This study examined the role of companion animals in mental well-being by comparing pet owners and non-owners in selected areas of Cavite and by exploring how emotional attachment to pets relates to well-being among owners. Grounded in biophilia, attachment, and ecotherapy perspectives, the study addressed whether having a companion animal supports healthier emotional functioning. A descriptive-comparative-correlational research design was employed. Data were collected using standardized self-report measures of mental well-being and pet attachment and were analyzed through chi-square tests and Spearman correlation analysis. Results revealed a significant difference in mental well-being between groups. A majority of pet owners reported above-average mental well-being, while most non-owners fell within the average range, with the difference reaching statistical significance. Among pet owners, levels of attachment varied across domains, with higher emotional closeness and reliance on pets compared to lower engagement in animal welfare and rights. Correlation analyses showed that all attachment domains were positively and significantly associated with mental well-being, indicating that stronger emotional bonds with pets consistently aligned with higher psychological well-being. Based on these findings, the program “FURtitude FUR-ever Well” was developed to promote mental well-being through structured therapy-animal interactions, relaxation activities, community involvement, and responsible pet care. Overall, the study highlights companion animals as meaningful emotional supports and underscores the importance of the quality of bond between human and animal in fostering mental well-being.